A Bibliometric Analysis of Career Aspiration of South Asian Youth - Shrestha, Hira Lal; Anas, Muhammed (NPRC Journal of Multidisciplinary Research, 2026)
Background: Career transitions of youth in Nepal and India happen amidst increasing educational aspirations, joblessness, labor market mismatch, and considerable international mobility. Even though increased focus is being laid on the issue by policymakers, there have been very few systematic bibliometric studies in this research area.Objectives: This study aimed to (1) perform a bibliometric analysis of career choices of youth in Nepal and India (2021–2025), (2) study the citation analysis, (3) study the author collaboration network, (4) perform bibliographic coupling analysis of these two countries, and (5) undertake the co-citation analysis of journals.Methodology: A systematic search was performed using the keyword search strategy of Boolean logic: ("career choice" OR "career aspiration" OR "job selection") AND ("youth" OR "adolescent" OR "young adult") AND ("Nepal" OR "India"). Based on PRISMA principles, out of 26,756 results, a total of 676 gold open-access journal articles from 2021 to 2025 were included. Analysis was done using VOSViewer.Results: The number of publications grew by 116% from 94 (2021) to 203 (2025), experiencing a significant 52.3% increase in 2024. Citation levels were consistently high between 2021 and 2022 (>88%), although citation rates fell to 43.84% for 2025 owing to the citation lag phenomenon. In the co-authorship analysis, a tight-knit, Bangladesh-centred research cluster emerged, with only a few Nepalese and Indian authors involved. Bibliographic coupling produced a core-periphery framework, with the USA, India, China, and UK serving as central nodes. Three thematic clusters were found in co-citation analysis: psychology/behavioural, sustainability/entrepreneurship, and education.Conclusion: The study reveals a surge in research on youth career options in Nepal and India; however, there is spatial concentration and minimal involvement of regional authors, underscoring the importance of regional research collaborations.Novelty: This is the first bibliometric review of youth career studies specifically focusing on Nepal and India using VOSviewer and PRISMA-based open-access screening.